Broadband X-ray analysis of 1E 1740.7−2942: constraints on spin, inclination, and a tentative black hole mass - Stecchini, Paulo E; D’Amico, F; Jablonski, F; Castro, M; Braga, J (Monthly notices of the Royal Astronomical Society, 2020)
1E 1740.7−2942 is one of the strongest hard X-ray emitters in the Galactic Centre region, believed to be a black hole in a high-mass X-ray binary system. Although extensively studied in X-rays, many aspects about the underlying nature of the system are still unknown. For example, X-ray data analyses of 1E 1740.7−2942 to date have not yet unveiled the signature of a reflection component, whose modelling could be used to estimate parameters such as the spin of the black hole and inclination of the disc. We report here on the determination of these parameters from the analysis of the reflection component present in a public NuSTAR observation which has not been subject to any previous study. We include XMM–Newton and INTEGRAL data to build a combined spectrum, enabling a joint analysis of both the disc and comptonization components. Results point to a relatively high inclination disc ≳ 50° (3 σ) and a near-maximum speed rotating black hole. The former is in agreement with a previous radio study and the latter is reported here for the first time. Lastly, we follow the methodology of recent efforts to weigh black holes with only X-ray spectra and find results that suggest a black hole mass of about 5 M⊙ for 1E 1740.7−2942.